PERSEPSI MAHASISWA TERHADAP MEDIA PEMBELAJARAN MINI CULTIVATOR PADA MATERI ELEMEN MESIN - Setiawan, Firman; Wiyogo, Wiyogo; Sukardi, Sukardi (Steam Engineering, 2024)
Starting from the limitations of real learning media in learning, this study aims to explore students' perceptions of the use of Mini Cultivator as a learning medium. The research method used is quantitative using the urgency, seriousness, and growth (USG) matrix. The data collection technique uses a questionnaire. The results of the study showed that students' perceptions on the aspect of media effectiveness received the highest priority with a percentage of 25.07%, followed by motivation at 25.06%, usefulness at 25.04%, and innovation at 24.81%. Students' positive perceptions of Mini Cultivator media are reflected in the results of the USG analysis. The results of the assessment on the "urgency" dimension indicate students' awareness of the importance of using Mini Cultivator in learning. The "usefulness" dimension shows that students see Mini Cultivator media not only as an addition, but as an important element in learning. The "development" aspect shows that Mini Cultivator media is relevant and closely related to the topic or concept being studied.